Modifiable Comorbidity as a Risk Factor for DRPs and Unimproved NIHSS Score in Ischemic Stroke Patients - FIRDHA APRILLIA WARDHANI (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Drug-related problems are problems that are often encountered in stroke patients because of the complex management of stroke therapy due to comorbidities. Research shows that 90% of stroke patients experience drug-related problems (DRPs). However, there was limited information regarding the effect of comorbidity as both a risk factor for DRPs prevalence and worse outcomes in an ischemic stroke patient. This research was conducted to see whether modifiable comorbidities indeed had a significant impact as a risk factor for DRPs and clinical outcomes in hospitalized ischemic stroke patients at a tertiary hospital in Indonesia during January 2020-October 2021. This study was conducted retrospectively using cross-sectional analysis, with the subject being the patient's medical record. This study found no significant relationship between the presence of comorbidities in patients with the incidence of DRPs. Diabetes mellitus was found to have a significant association with no improvement in NIHSS scores in ischemic stroke patients. In patients with diabetes mellitus, there is an increased risk of non-improvement NIHSS score 2,987 times compared to patients without diabetes mellitus. The second increased risk was the presence of comorbid hypertension (OR 1.361, 95% CI 0.598-3.095, p-value=0.463), and the third was dyslipidemia (OR 1.125, 95% CI 0.505-2.502, p-value=0.774).